2021
DOI: 10.1002/bies.202000339
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian regeneration and mammalian cancer: Similarities and contrasts from an evolutionary biology perspective

Abstract: Here we review and discuss the link between regeneration capacity and tumor suppression comparing mammals (embryos versus adults) with highly regenerative vertebrates. Similar to mammal embryo morphogenesis, in amphibians (essentially newts and salamanders) the reparative process relies on a precise molecular and cellular machinery capable of sensing abnormal signals and actively reprograming or eliminating them. As the embryo's evil twin, tumor also retains common functional attributes. The immune system play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…In this work, we have established the novel findings that squamates and amphibians both have a positive relationship between body mass and neoplasia prevalence, and amphibians also have a positive relationship between body mass, lifespan, and cancer. It has been proposed that regenerative capacities, as observed in some amphibian species, may be associated with tumor suppression mechanisms 28,29 , and that regeneration in amphibians, unlike mammals, does not necessarily result in increased cancer prevalence 30,31 . This hypothesis needs further exploration since we found that amphibians had lower neoplasia and cancer prevalence than mammals and squamates, but higher than birds.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we have established the novel findings that squamates and amphibians both have a positive relationship between body mass and neoplasia prevalence, and amphibians also have a positive relationship between body mass, lifespan, and cancer. It has been proposed that regenerative capacities, as observed in some amphibian species, may be associated with tumor suppression mechanisms 28,29 , and that regeneration in amphibians, unlike mammals, does not necessarily result in increased cancer prevalence 30,31 . This hypothesis needs further exploration since we found that amphibians had lower neoplasia and cancer prevalence than mammals and squamates, but higher than birds.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, similarities between early embryo development and tumorigenesis exist, with respect to cell invasive behavior and genetic/epigenetic regulation 68 , 69 which provide the opportunity to exploit developmental biology to identify potential targets against tumor initiation and progression. 1 This work not only highlights the anti-tumor potential of MSCs from gestational tissues. It also sheds light on the different responses SKOV-3 and OVCAR-3 activate as coping molecular mechanisms against the MSCs derivatives.…”
Section: Discussionmentioning
confidence: 74%
“…The tumor is commonly conceived as the “evil twin of the embryo,” due to rapid rates of cellular proliferation and spreading, maternal immune system evasion, and the capability to act as a parasite for nutrient supply. 1 During morphogenesis the precise recapitulation of specific developmental steps and the immature status of the immune system, ensure the correct patterning for tissue growth by the continuous and regulated interplay between neighboring cells. 2 This controlled series of cellular interactions occurs in a well-lubricated environment, where the amniotic fluid (AF) carries proteins and or peptide(s) that can support organogenesis and offer a natural immune response against infections, and the chorionic villi (CV) has an important role in fetomaternal exchanges.…”
Section: Introductionmentioning
confidence: 99%